Shareholders’ Participation in the Affairs of Public Companies: An Insight (2010)
The aim of this study was to have an insight into the participation of shareholders in the affairs of public companies. The information gathered in relation to this study revealed that the only way shareholders can actively participate in the affairs of public companies was by attending the Annual General Meeting (AGM) and exercise the powers reserved for them. However, as a matter of law, there is no enforceable obligation on the shareholders to attend the AGM of their companies for that matter, or indeed, actively participate in the affairs of the company, but such shareholders remain bound by any decision the meeting may take, their nonparticipation notwithstanding. Conclusively, the study submitted that active participation of shareholders in the AGM is capable of saving their companies from possible lapses that may be as a result of mismanagement. Therefore shareholders should attend meetings of their companies, mostly the AGM